2022
DOI: 10.3390/w14233852
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the Data Gap between the GRACE Missions and Assessment of Groundwater Storage Variations for Telangana State, India

Abstract: Because of changing climatic conditions, uneven distribution of rainfall occurs throughout India. As a result, dependence on groundwater for irrigation has increased tremendously for industrial and domestic purposes. In India approximately 89% of agricultural demands are met through groundwater. Due to increases in population, demand for groundwater and lack of effective utilization have resulted in rapid depletion of groundwater in most parts of the country. Therefore, quantifying groundwater resources is a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Beneficiaries used 18 hrs/ha which was higher than non-beneficiaries as they were using 16.5 hrs/ha. Chinnapa et al, (2018) [9] also reported similar findings that farmer's dependency on animal and human labour was less by 16.29 percent and 68.30 percent respectively in case CHC villages compared to villages not covered by CHC. In the case of beneficiaries, family labour use was 9.7 percent more compared to non-beneficiaries of CHC.…”
Section: Results and Discussion Input Use Pattern In Groundnut Cultiv...mentioning
confidence: 74%
“…Beneficiaries used 18 hrs/ha which was higher than non-beneficiaries as they were using 16.5 hrs/ha. Chinnapa et al, (2018) [9] also reported similar findings that farmer's dependency on animal and human labour was less by 16.29 percent and 68.30 percent respectively in case CHC villages compared to villages not covered by CHC. In the case of beneficiaries, family labour use was 9.7 percent more compared to non-beneficiaries of CHC.…”
Section: Results and Discussion Input Use Pattern In Groundnut Cultiv...mentioning
confidence: 74%
“…These two missions provide a unique tool for determining the temporal variations of gravity; consequently, the mass redistribution processes that have generated the gravity changes [4]. GRACE and GRACE-FO have become essential sources of data when monitoring the variation in water fluxes over large basins (e.g., the Mediterranean Sea [5], the Arabian Peninsula [6][7][8], Niger [9], Michigan [10], the Amazonas [11][12][13], the La Plata basins [14,15], the Nubian and Nile basins [16][17][18][19][20][21]), and for the analysis of climate changes via ice mass balance [22][23][24], sea level rise [25,26], ground water storage [27][28][29][30][31], and extreme precipitation [32]. In the present study, a GRACE-and GRACE-FO-based gravity anomaly time series is determined and utilized to analyze the desiccation process of the Aral Sea.…”
Section: Introductionmentioning
confidence: 99%